Peran Literasi Keuangan Dalam Meningkatkan Usaha Masyarakat Disabilitas Perempuan Di Malang Raya - Wiyarni, Wiyarni; Pudjiastuti, Widanarni; Sudjawoto, Eko; Wijaya, Sella Septian; Saputra, Damar Auliawan (Jurnal ABM Mengabdi, 2025)
In this era of globalization, financial literacy has become an essential skill for all levels of society to achieve economic independence. Moreover, financial literacy skills play an important role in supporting business success, especially for community groups who have limited access to information and economic opportunities, such as women with disabilities. The Community Service Program (PKM) is an effort to reach communities that have received little attention, especially universities and academics. This PKM aims to improve the businesses of women with disabilities in the Greater Malang area. Activities carried out include financial literacy training on the importance of separating personal or household transactions from business transactions in order to measure business progress. It is hoped that this training can improve the businesses of women with disabilities in Greater Malang.